Basics of Web Hacking : Tools and Techniques to Attack the Web. - Pauli, Joshua J. (Elsevier Science & Technology, 2013)
The Basics of Web Hacking introduces you to a tool-driven process to identify the most widespread vulnerabilities in Web applications. No prior experience is needed. Web apps are a ""path of least resistance"" that can be exploited to cause the most damage to a system, with the lowest hurdles to overcome. This is a perfect storm for beginning hackers. The process set forth in this book introduces not only the theory and practical information related to these vulnerabilities, but also the detailed configuration and usage of widely available tools necessary to exploit these vulnerabili.